Dasineura asteriae Reprograms the Flower Gene Expressions of Vegetative Organs to Create Flower-Like Gall in Aster scaber - Boo, Kyung-Hwan; Oh, Young Kyoung; Møller, Christian; Lee, Doseung; Jeon, Gyeong Lyong; Kim, Donghyuk; Burow, Meike; Großkinsky, Dominik Kilian; Kim, Jiwon; Ryu, Moon Young; Lee, Bora; Suh, Jiye; et al. (Plant, cell & environment, 2025)
Plant galls are abnormal growing tissues induced by various parasitic organisms, exhibiting diverse and complex morphologies. Typically, these galls differ significantly in appearance from their host plants. Here, we report that larvae of a parasitic fly generate unique, rosette galls on Aster scaber, a perennial herb. These galls develop from vegetative organs after the larvae reprogram floral gene expression. To investigate the underlying mechanisms, we conducted whole-genome sequencing and transcriptome analysis. Our findings reveal that the larvae induce host organ dedifferentiation into an amorphous callus, activate floral genes, and selectively suppress genes associated with carpel development. As a result, the pseudoflowers consist solely of tepal-like leaflets and a specialized chamber, and the larvae influence pigment biosynthesis. Hijacking plants developmental gene networks by insects to sequentially mediate dedifferentiation, cytokinin regulation, and tepal-like leaflets formation provides a framework to study highly elaborate forms of parasitism and symbiosis between plants and insects.
Keywords: Flowers; Plant Tumors; květy; larva; interakce hostitele a parazita; redifferentiation; zvířata; regulace genové exprese u rostlin; Droseraceae; floral reprogramming; plant‐insect interaction; insect‐induced plant gall; Animals; Larva; Gene Expression Regulation, Plant; nádory rostlin; Host-Parasite Interactions